Performance analysis of snail shell biomaterials in solar still for clean water production: Nature-inspired innovation for sustainability - Dhivagar, Ramasamy; Suraparaju, Subbarama Kousik; Atamurotov, Farruh; Kannan, Kalimuthu Gopi; Opakhai, Serikzhan; Omara, Adil A. M. (IWA Publishing, 2024)
In this current investigation, the experimental performance of a solar still basin was significantly enhanced by incorporating snail shell biomaterials. The outcomes of the snail shell-augmented solar still basin (SSSS) are compared with those of a conventional solar still (CSS). The utilization of snail shells proved to facilitate the reduction of saline water and enhance its temperature, thereby improving the productivity of the SSSS. Cumulatively, the SSSS productivity was improved by 4.3% over CSS. Furthermore, the SSSS outperformed in energy and exergy efficiency of CSS by 4.5 and 3.5%, respectively. Economically, the cost per liter of distillate (CPL) for the CSS was 3.4% higher than SSSS. Moreover, the SSSS showed a shorter estimated payback period (PBP) of 141 days which was 6 days less than CSS. Considering the environmental impact, the observed CO2 emissions from the SSSS were approximately 14.6% higher than CSS over its 10-year lifespan. Notably, the SSSS exhibited a substantial increase in the estimated carbon credit earned (CCE) compared to the CSS. Ultimately, the research underscores the efficacy of incorporating snail shells into solar still basins as a commendable approach to organic waste management, offering economic benefits without compromising environmental considerations.